Particle shape accounts for instrumental discrepancy in ice core dust size distributions - Simonsen, Marius Folden; Cremonesi, Llorenç; Baccolo, Giovanni; Bosch, Samuel; Delmonte, Barbara; Erhardt, Tobias; Kjær, Helle Astrid; Potenza, Marco; Svensson, Anders; Vallelonga, Paul (Climate of the Past, 2018)
The Klotz Abakus laser sensor and the Coulter Counter are both used for measuring the size distribution of insoluble mineral dust particles in ice cores. While the Coulter Counter measures particle volume accurately, the equivalent Abakus instrument measurement deviates substantially from the Coulter Counter depending on the type of sample. We show that the difference between the Abakus and the Coulter Counter measurements is mainly caused by the irregular shape of dust particles in 5 ice core samples. The irregular shape leads means that the calibration routine based on standard spheres must be adjusted. This new calibration routine gives an increased accuracy on Abakus measurements, which may improve future ice core record intercomparisons. We derived an analytical model for extracting the aspect ratio of dust particles from the difference between Abakus and Coulter Counter data. For verification, we measured the aspect ratio of the same samples directly using a Single Particle Extinction and Scattering Instrument. The results demonstrate that the model is accurate enough to discern between 10 samples of aspect ratio 0.3 and 0.4 using only the comparison of Abakus and Coulter Counter data.